Identification and Expression Analysis of the DHN3 Gene during the Core Browning of Late-Harvested Yali Pears (Pyrus bretschneideri Rehd.) - KOU Xiaomin, LI Qingxiu, LI Ling, ZHANG Chenyun, YAN Shijie, LIANG Liya, DENG Bing (Shipin Kexue, 2023)
In order to explore the relationship between dehydrin (DHN) and core browning in late-harvested Yali pears, this study identified and characterized the PbDHN3 gene based on bioinformatics methods, and analyzed the expression pattern of this gene during the core browning process under rapid cooling and slow cooling conditions. The results showed that the open reading frame (ORF) of PbDHN3 was 564 bp in length, encoding 187 amino acids, and having a conserved domain of dehydrin superfamily comprising two Y segments, one S segment and three K segments (Y2SK3). Bioinformatics analysis showed that PbDHN3 was a hydrophilic stable protein with a molecular mass of 19.77 kDa and an isoelectric point of 7.98. The secondary structure consists of α-helix, irregular coil, extended chain and β-turn. PbDHN3 was located in the nucleus and contained no signal peptide or transmembrane structure. It was a non-secretory protein. The results of homology analysis showed that PbDHN3 was more than 89.74% similar to the DHN of five other plants such as apples. Phylogenetic analysis showed that PbDHN3 had the closest relationship with the DHN of Pyrus ussuriensis × Pyrus communis. The results of promoter analysis showed that PbDHN3 contained basic promoter elements and other cis-acting elements, which were consistent with the predicted results of the upland cotton GhDHN1 and the wheat TaDHN2 promoter regions, and all of them included hormone response elements and light response elements. The results of real-time fluorescence polymerase chain reaction (PCR) analysis showed that the expression of the DHN3 gene was significantly up-regulated during the core browning process of Yali pears under rapid cooling conditions, which was closely related to the browning of the core. This study provides a theoretical basis for further exploring the function of the PbDHN3 gene and clarifying the mechanism of core browning of Yali pears.